Tarascan copper metallurgy : a multiapproach perspective - Maldonado, Blanca, (Archaeopress pre-Columbian archaeology ;, 2018)
This is a study which provides valuable insights into the nature of metal production and the development of technology and political economy in ancient Mesoamerica, offering a contribution to general anthropological theories of the emergence of social complexity.